PEMBERDAYAAN REMAJA HEALTH LITERACY BERBASIS BOARD GAME MENINGKATKAN PENGETAHUAN KONSUMSI JUNK FOOD - Hardiyanti, Siti; Ramadhani, Dwi Yuniar; Rahayu, Putri Sukma (PPM STIKES Adi Husada, 2026)
Introduction & Aim: Many adolescents have a habit of consuming junk food due to its taste and convenience. Excessive consumption can lead to various health problems such as obesity, digestive disorders, and an increased risk of chronic diseases. This community service aimed to improve adolescents’ knowledge and awareness of the impacts of junk food consumption through a health literacy approach. Method of Activity: This activity was conducted in the Tenggumung Wetan area of Surabaya, involving 21 adolescents aged 14–20 years. The activity began with a baseline survey and was followed by health education using an interactive approach. Participants completed a knowledge questionnaire regarding junk food consumption before the educational session. The educational intervention was delivered through the screening of educational videos and the use of the GIVIC board game as an interactive learning tool. Results: An increase in adolescents’ knowledge following the health education session. Knowledge levels rose from 42.85% before the activity to 57% afterward. Respondent characteristics were dominated by adolescents aged 17–18 years (42.82%), females (61.90%), and high school graduates (66.67%). Discussion: Health literacy-based health education using interactive learning media, such as educational videos and board games, can improve adolescents’ knowledge of the dangers of consuming junk food. These methods can increase participants’ active engagement, reinforce understanding, and help adolescents retain the health information provided.